Temporal Sequence Learning in Healthy Aging and Amnestic Mild Cognitive Impairment - Pirogovsky, Eva (2013)
BACKGROUND/STUDY CONTEXT: Temporal sequence learning is a critical aspect of episodic memory that may be dependent on the temporal and frontal lobes. Since amnestic mild cognitive impairment (aMCI) and normal aging may result in changes within the temporal and frontal lobes, the present study investigated temporal sequence learning in patients with aMCI, cognitively normal older adults, and young adults. METHODS: On each trial of a temporal sequence task, circles appeared one at a time at the end of each arm of a computerized radial 8-arm maze. Participants were asked to reproduce the temporal sequence by placing numbered circles (1-8) on the arms of the 8-arm maze. Participants were presented with the same fixed sequence on each trial until the sequence was replicated without any errors, or until 15 trials were presented. RESULTS: Individuals with aMCI required significantly more trials to learn the temporal sequence compared to older adults (p <. 05). Older adults required significantly more trials to learn the sequence than young adults (p <. 05). Older adults and individuals with aMCI committed significantly more Trial 1 errors (p <. 05) than young adults; however, there were no significant differences between the aMCI and older adult groups on Trial 1. CONCLUSION: The results suggest that temporal sequence learning deficits are detectable in aMCI. These deficits may disrupt a number of cognitive processes, such as episodic memory, that are important for the execution of daily activities. The results suggest that although temporal sequence learning declines with normal aging, this decline is greater in individuals who have a diagnosis of aMCI and are at higher risk for developing AD.